Development of Agro Tourism Conceptual Areas: Foreign Experience - Amirov Akmal Merojovich; Amirova Dinora Akmalovna (Indonesian Journal of Law and Economics Review, 2020)
This article describes the nature, causes, types and characteristics of agro-tourism in foreign countries. In addition, the basic concepts of agro-tourism development, as well as examples of national associations are provided. Along with countries that have positive experience in the field of agro tourism, many countries that are actively developing this experience have made suggestions and suggestions on its development.